Photophysics of deinoxanthin, the keto-carotenoid bound to the main S-layer unit of Deinococcus radiodurans. Issue 4 (1st April 2020) - Adamec, František; Farci, Domenica; Bína, David; Litvín, Radek; Khan, Tuhin; Fuciman, Marcel; Piano, Dario; Polívka, Tomáš
Abstract : An ultrafast transient absorption experiment on the SDBC, which binds the carotenoid deinoxanthin, reveals a non-specific binding site that loosely binds the carotenoid, but protects the carotenoid from the outer environment. Abstract : The keto-carotenoid deinoxanthin, which occurs in the UV-resistant bacterium Deinococcus radiodurans, has been investigated by ultrafast time-resolved spectroscopy techniques. We have explored the excited-state properties of deinoxanthin in solution and bound to the S-layer Deinoxanthin Binding Complex (SDBC), a protein complex important for UV resistance and thermostability of the organism. Binding of deinoxanthin to SDBC shifts the absorption spectrum to longer wavelengths, but excited-state dynamics remain unaffected. The lifetime of the lowest excited state (S1 ) of isolated deinoxanthin in methanol is 2.1 ps. When bound to SDBC, the S1 lifetime is 2.4 ps, indicating essentially no alteration of the effective conjugation length upon binding. Moreover, our data show that the conformational disorder in both ground and excited states is the same for deinoxanthin in methanol and bound to SDBC. Our results thus suggest a rather loosely bound carotenoid in SDBC, making it very distinct from other carotenoid-binding proteins such as Orange Carotenoid Protein (OCP) or crustacyanin, both of which significantly restrain the carotenoid at the binding site. Three deinoxanthin analogs were found to bind the SDBC, suggesting a non-selective binding site of deinoxanthin in SDBC.